PERBANDINGAN KEAKURATAN LABA PERMANEN, LABA AGREGAT, DAN ARUS KAS OPERASI UNTUK MEMPREDIKSI ARUS KAS OPERASI MASA DEPAN - Evana, Einde; Thiono, Silvia (Journal of Accounting and Investment, 2009)
The goal of this research is to compare the accuracy of three prediction models which are permanent earnings, aggregate earnings and operational cash flow in prediction future operational cash flow. The hypotheses which are proposed in this research are H1: permanent earnings are more accurate than aggregate earnings in prediction future operational cash flow, and H2: operational cash flow is more accurate than aggregate earnings in prediction future operational cash flow. The researcher uses test instruments panel data regression to make efficient regression panel data model. The samples in this research are 29 companies from 148 manufactory companies which are registrant in Indonesian Stock Exchange. The dependent variable is operational cash flow, whereas independent variables are permanent earnings, aggregate earnings and operational cash flow. The accuracy comparison of prediction model is done by comparing the value of prediction error by using absolute percentage error (APE). The result of test by using Wilcoxon Signed Rank Test with realÂ  rate 5% prove that permanent earnings is not different from the accuracy with aggregate earnings in prediction future operational cash flow. Empirical evidence also shows that operational cash flow is more accurate than aggregate earnings in prediction future operational cash flow.